2011
DOI: 10.2478/v10035-011-0059-8
|View full text |Cite
|
Sign up to set email alerts
|

Elective Resection of Rectal Cancer Primary Tumor in Patients with Stage IV Disease - Own Experiences

Abstract: In properly selected group of patients elective resection of primary tumor may cause low mortality rate and acceptable morbidity rate. This surgical modality allows to avoid potential complications of tumor local growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Unless there are specific indications for acute management of the primary in this setting, provided that patients are under surveillance the majority will not require emergent surgery for intestinal obstruction and/or perforation [32]. Although some studies have demonstrated a survival benefit for primary resection [33], the data are biased towards patients with a better performance status and better prognosis (less metastatic sites involved).…”
Section: Patients With Unresectable Metastasesmentioning
confidence: 99%
“…Unless there are specific indications for acute management of the primary in this setting, provided that patients are under surveillance the majority will not require emergent surgery for intestinal obstruction and/or perforation [32]. Although some studies have demonstrated a survival benefit for primary resection [33], the data are biased towards patients with a better performance status and better prognosis (less metastatic sites involved).…”
Section: Patients With Unresectable Metastasesmentioning
confidence: 99%